Analysis of Marketing Mix Strategy in Increasing Sales Volume at Bu Nurhayati's Rengginang Outlet in Pahang Village, Batu Bara Regency - Sari, Maya; Agustin, Roro Rian; Budiharto, Toto (Journal of Community Research and Service, 2024)
This research was conducted on the Rengginang Bu Nurhayati outlet business with the aim of analyzing the marketing mix strategy in increasing sales volume in the business activities carried out. The type of research used is qualitative descriptive, the type of data used is secondary data. Data collection techniques were used, namely literature studies, interviews, observations and documentation. The data analysis technique uses qualitative descriptive. The results of the research obtained show that the marketing mix strategy at the Rengginang Bu Nurhayati business outlet is still not fully running optimally. This can be seen from the policy carried out by Bu Nurhayati who does not promote using trendy social media, so that rengginang products cannot be known and accessed by people outside the rural areas of Pahang, Batu Bara Regency and are only known by the surrounding community and people who pass through the area. In addition, business owners do not carry out distribution channels to other parties so that there is no cooperation in the distribution of Bu Nurhayati rengginang products so that consumers who want to sell the product must come directly to the business location. The suggestion that can be conveyed is that in the future, Bu Nurhayati should be able to use one of the online promotional media such as Facebook or IG to introduce his product to people outside the region so that the product can be interested and purchased by the community according to their needs. The existence of online promotional media , consumers or people from outside the region can access information about the types and variants of products sold so that it can be an alternative for people to buy these products as souvenirs to replace other goods that have added value and can be consumed for family and relatives.